PENERAPAN WINDOW SHOPPING BERBANTU APLIKASI CANVA UNTUK MENINGKATKAN HASIL BELAJAR NEGARA ANGGOTA ASEAN - Mustofa, Henri; Zulfiati, Heri Maria; Wibawa, Sutrisna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The use of learning models that are less attractive causes low student learning outcomes. This research aims to improve student learning outcomes through interactive and fun learning through the application of the window shopping learning model. This learning is more interesting by using the Canva application as a supporting element. The type of research used was descriptive qualitative with the research subjects being 6th grade students in elementary schools, totaling 37 students consisting of 19 male students and 18 female students. This type of qualitative descriptive research uses data collection techniques such as tests, questionnaires, observation and documentation. Data analysis techniques use quantitative and qualitative analysis. This window shopping learning model has proven effective in improving student learning outcomes regarding material from ASEAN member countries. This is evidenced by the increase in student learning outcomes from 16 students by 43.24% with the lowest score being 35 and the highest score being 85 to 31 students amounting to 83.78% with the lowest score being 50 and the highest score being 100. The average score of student learning outcomes has increased from 63.32 to 82.78.